2018
DOI: 10.3389/fpsyg.2018.01927
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Action Retrospectively but Not Prospectively Alters Emotional Judgment

Abstract: Metaphorical association between vertical space and emotional valence is activated by bodily movement toward the corresponding space. Upward or downward manual movement “following” observation of emotional images is reported to alter the perceived valence as more positive or negative. This study aimed to clarify this retrospective emotional modulation. Experiment 1 investigated the effects of temporal order of emotional stimuli and manual movements. Participants performed upward, downward, or horizontal manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 42 publications
1
40
0
2
Order By: Relevance
“…Supporting this notion, bodily movements to enact a metaphor that represents an association between abstract concepts can also modulate cognition (i.e., embodied cognition). For instance, arm movements in a vertical direction, which represent a metaphorical association between vertical space and emotional valence (e.g., up-good, down-bad), can bias the recollection of emotional autobiographical memory [8] and evaluation of a previous emotional stimulus [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this notion, bodily movements to enact a metaphor that represents an association between abstract concepts can also modulate cognition (i.e., embodied cognition). For instance, arm movements in a vertical direction, which represent a metaphorical association between vertical space and emotional valence (e.g., up-good, down-bad), can bias the recollection of emotional autobiographical memory [8] and evaluation of a previous emotional stimulus [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, Sasaki et al found that vertical manual action retrospectively affects the valence rating of the stimuli; however, it was still unknown that manual action can prospectively affect the valence rating. Thus, authors (Kato, Imaizumi, & Tanno, 2018) replicated Sasaki et al with the condition where vertical manual action was introduced before the stimuli presentation.…”
Section: Introductionmentioning
confidence: 87%
“…Consequently, Kato et al (2018) revealed that the valence rating was only affected retrospectively by the vertical manual action but not prospectively. Then, can we conclude that vertical manual action does not affect the processing of emotional stimuli at all?…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When experimental stimuli are changed from words to sentences (Marmolejo-Ramos et al, 2014), pictures and faces (Elizabeth Crawford et al, 2006; Mahieu et al, 2014), such metaphor-consistent effect holds true. This effect has also been consolidated in various tasks, involving on-line evaluation (Meier and Robinson, 2004), memory (Crawford et al, 2014), eye-tracking (Gozli et al, 2013), physical movements (Kato et al, 2018), and 3D-space tasks which extend the valence-space metaphor effect to the dimension of 3D space (Marmolejo-Ramos et al, 2018, 2019). Furthermore, the affective perceptual–conceptual associations have been verified when other physical dimensions are involved, including brightness (Meier et al, 2004, 2015; Lakens et al, 2012; Huang et al, 2018), pitch (Weger et al, 2007), taste (Meier et al, 2012), size (Meier et al, 2008), and weight (Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%